2022
DOI: 10.3390/ani12030335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Body Weights and Egg Production Traits Using a Multi-Trait Animal Model and Selection Index in Thai Native Synthetic Chickens (Kaimook e-san2)

Abstract: To improve the genetics of both growth and egg production, which are limitations in purebred native chickens, new genetic lines can be developed using an appropriate genetic approach. The data used in this study included 2713 body weight (BW0, BW4, BW6, BW8, and BW10), breast circumference (BrC6), chicken age at first egg (AFE), and egg production (240EP, 270EP, 300EP, and 365EP) records covering the period 2015 to 2020. A multi-trait animal model with the average information-restricted maximum likelihood (AI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
5
16
0
1
Order By: Relevance
“…The heritability estimates for the BW, ADG, and BrC traits in the present study were medium to high (ranging from 0.204 to 0.499; see Table 1 ), which was similar to the results of studies carried out on local Venda chickens [ 29 ], Mazandaran native chickens [ 44 ], and purebred [ 13 , 14 ] and crossbred Thai native chickens [ 45 , 46 ]. The heritability for body weight was highest at eight weeks of age (BW8), not including birth weight (BW0), and the values tended to decrease with increasing age.…”
Section: Discussionsupporting
confidence: 88%
“…The heritability estimates for the BW, ADG, and BrC traits in the present study were medium to high (ranging from 0.204 to 0.499; see Table 1 ), which was similar to the results of studies carried out on local Venda chickens [ 29 ], Mazandaran native chickens [ 44 ], and purebred [ 13 , 14 ] and crossbred Thai native chickens [ 45 , 46 ]. The heritability for body weight was highest at eight weeks of age (BW8), not including birth weight (BW0), and the values tended to decrease with increasing age.…”
Section: Discussionsupporting
confidence: 88%
“…When comparing the body weights of KKU1 and KKU2 chickens to those of indigenous chickens in other countries, it was found that KKU1 and KKU2 chickens have a four-and three-times higher body weight than Horro chickens in Ethiopia [20] at 6 weeks, as well as compared to local Venda chickens in South Africa [21] and Mazandaran indigenous chickens [22]. In crossbred chickens, the body weight at all ages (BW2, BW4, and BW6) of both the KKU1 and KKU2 chickens was higher than that reported in crossbred Chinese indigenous [23], crossbred Italian indigenous [24], crossbred Indian indigenous [25], and Thai synthetic chickens [1,10,11]. The differences depend on the genetics of the animals, selection program, and feed and feeding, in addition to environmental differences.…”
Section: Discussionmentioning
confidence: 74%
“…From a marketing perspective, indigenous chicken meat has been proven to stand out in many respects, such as its good-quality meat, delicious taste, and use as a health food [8][9][10]. However, the main disadvantage of indigenous chickens is their slow growth [5,11,12]. As a result, it takes longer to raise them to market weight.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to KU-Phuparn (Thai black-bone chicken) [38], the CB × CB chickens in this research showed a higher body weight at 12 weeks of age. Meanwhile, Thai native chickens have developed a genetic improvement in the optimal market size at 1200 g [13,17]. The Hmong black-bone chicken is a native chicken with a small body size classified as wildfowl or mountain fowl.…”
Section: Discussionmentioning
confidence: 99%
“…Native chickens are indigenous animals distributed throughout the world, especially in rural communities [13][14][15]. Many academic data support Thai native and black-bone chicken meat quality as healthy foods [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%